Differences in ultrasound‐derived arterial wall stiffness parameters and noninvasive blood pressure between Friesian horses and Warmblood horses - Vera, Lisse (J Vet Intern Med, 2020)
BACKGROUND: Aortic rupture is more common in Friesians compared to Warmbloods, which might be related to differences in arterial wall composition and, as such, arterial wall stiffness (AWS). Currently, nothing is known about differences in AWS between these breeds. OBJECTIVES: Comparison of AWS parameters and noninvasive blood pressure between Friesians and Warmbloods. ANIMALS: One hundred one healthy Friesians and 101 age‐matched healthy Warmbloods. METHODS: Two‐dimensional and pulsed‐wave Doppler ultrasound examination was performed of the aorta, common carotid artery, and external iliac artery to define local and regional AWS parameters. Regional aortic AWS was estimated using aortic‐to‐external iliac artery pulse wave velocity (PWV(a‐e)) and carotid‐to‐external iliac artery pulse wave velocity (PWV(c‐e)). Noninvasive blood pressure and heart rate were recorded simultaneously. RESULTS: Systolic, diastolic, and mean arterial blood pressure and pulse pressure were significantly higher in Friesians compared to Warmbloods. No significant difference in heart rate was found. Most local AWS parameters (diameter change, compliance coefficient, distensibility coefficient) were significantly lower in Friesians compared to Warmbloods, indicating a stiffer aorta in Friesians. This difference could be confirmed by the regional stiffness parameters. A higher PWV(a‐e) and PWV(c‐e) was found in Friesians. For the cranial and caudal common carotid artery and external iliac artery, most local AWS parameters were not significantly different. CONCLUSIONS AND CLINICAL IMPORTANCE: Results indicate that aortic AWS differs between Friesian and Warmblood horses. Friesians seem to have a stiffer aorta, which might be related to the higher incidence of aortic rupture in Friesians.